Strategies Unveiled: A Comprehensive Analysis of Teaching Speaking Skills in the Context of Madrasah Aliyah - Ikbal, Muhammad; Permana, Dio Resta; Sirayatika, Desi (ELT Worldwide: Journal of English Language Teaching, 2024)
This study investigates the teaching strategies employed at MA Al-Hidayah Muara Telang, focusing on enhancing students' English speaking skills. Through qualitative analysis of classroom observations and interviews with two English teachers, the research identifies a range of strategies including Dialogue, Questions and Answers, Conversation, Role-plays, Writing Tasks, and Drilling and Chant. These methods aim to foster student engagement, improve language proficiency, and encourage active participation in the learning process. The findings reveal a consistent use of interactive and communicative strategies by the teachers to create an engaging learning environment. However, challenges such as limited student participation, anxiety about speaking English, reliance on native language, and passive behavior in class were observed. These issues highlight the complexities of teaching and learning English as a second language and the need for approaches that boost confidence and participation. The study suggests incorporating supportive teaching practices, promoting a positive classroom atmosphere, and diversifying communicative activities to address these challenges. It underscores the importance of adaptability in teaching strategies to meet diverse student needs and enhance the effectiveness of English language education. This research contributes to the discourse on English language teaching, emphasizing the critical role of interactive strategies and the psychological aspects of language learning. It calls for further exploration into innovative methods to enrich English language teaching and learning experiences at MA Al-Hidayah Muara Telang and similar educational contexts.